QUALIDADE PERCEBIDA DA INTRANET: UM ESTUDO DE CASO NUMA EMPRESA DE TELECOMUNICAÇÕES - Campos, Flávio de Moraes Siqueira (2008)
The technologic innovation in the computation and communication industry led appear the big network named Internet which, in the last years, gaves great changes in the way of people to communicate, divulge knowledge, do business and transactions with money, as well as other applications everyday surging. The technological basis of Internet quickly lead people think to bring the benefits of big network into the organizations, giving raise Intranet. With an obvious sinergic importance in the stages of the value chain, the managers giving more and more importance to services supplied to internal customers , it becames fundamental to improve instruments to measure the quality of these services. This work consolidates a search in a great telecommunications enterprise with the purpose to know the performance of intranet by appraising the performance measure of that services, according perceived quality by the users and suppliers (Technology Support Group), using the modified SERVQUAL scale, also appraising the gap between the two perceptions (gap3 of conceptual model of Kang and Bradley). The used methodology, general conditions, new searches suggestions and mentioned and looked in bibliography also are part of the work.